Accumulation of irreversible deformation of soils as a result of repeated loading - K. G. Kondrashin; R. A. Petrov; N. A. Raktovich (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The purpose of the study is to establish the patterns of accumulation of irreversible soil deformations from repeated loading.Method. When loading soils, the balance between external and internal forces is established gradually over a more or less long time. Therefore, with a single application of a cyclic load, such an equilibrium can be achieved only in a relatively long time.Result. An approximate method is proposed for calculating the magnitude of the deformation developed as a result of the action of a cyclic load. The cases are determined when it is necessary to take into account the viscous component of deformation and when the latter can be neglected. It has been established that when determining the deformation of soils that has developed during a single application of such cyclic loads that are characteristic of the process of their compaction by machines, in all cases, except for rolling them with rollers on pneumatic tires, the viscous component of deformation can be ignored.Conclusion. In a relatively short time of the load, the state of equilibrium can be achieved only in the process of soil deformation by repeated loading. With an increase in the number of loading repetitions, the soil gradually hardens, and the deformation decreases. This occurs both due to the irreversible and reversible parts of the deformation. Consequently, the soil deformation modulus increases from cycle to cycle.